Autism and gender diversity in young adults: How gender stereotypes influence underdiagnosis (Research, Society and Development, 2024)
Objective: To gather scientific evidence on healthcare professionals' knowledge and its relation to gender stereotypes in the diagnosis of Autism Spectrum Disorder (ASD) in Brazil. Method: An integrative review in 6 stages conducted between April and May 2024 using the databases Google Scholar, PubMed, and ScienceDirect. Inclusion criteria were studies published from 2020 onwards, with at least two descriptors, and in Portuguese, English, or Spanish. Eligible studies were discussed and presented in tables. Results: From the 8 studies analyzed, two thematic classes emerged: "Autism and healthcare professionals'' and "Autism and gender diversity." Young adults on the autism spectrum tend to use techniques to mask their symptoms or express them unconventionally to adapt socially. This can lead to misdiagnosis, mainly due to the traditional literature's emphasis on symptoms more associated with males. There is a significant prevalence of neurodiverse individuals identifying as LGBT+. Conclusion: It was observed that healthcare professionals and academics need to develop a more comprehensive understanding of autism, especially considering its various manifestations beyond childhood. Given the gaps in autism and gender diversity in Brazil, there is a need for awareness initiatives, continuing education, training, and further research on the topic.